Reflections on the open or closed Alfierian studies; with some research and methodological perspectives (Prassi Ecdotiche della Modernità Letteraria, 2019)
After the international conference "Vittorio Alfieri: éditer, commenter, traduire", (Paris, 16 and 17 February 2018), the essay proposes some reflections on the most recent Alfierian bibliographical works (in progress or closed), opening some perspective for the future. In order to explore this field, an important condition is the possibility of having critical editions: the National Edition, promoted by the National Center of Alfierian Studies from 1951 and continued by the homonym Foundation, made a valid contribution. Taking a general look at the series, however, at least four works have required and require new critical editions: "Vita", the political treaties "Della Tirannide" and "Del Principe e delle Lettere" and "Rime". Another critical aspect is the lack of commented editions. Better results come from other studies, such as the survey on the Alfieri’s libraries, or the international project "Digital Alfieri", born in 2015 and still in progress. The opportunities that digital technologies combined with philology could provide, would also be very profitable for investigations in the correspondence. Finally, the philology of Alfierian translations, while appearing as a marginal aspect in the 'mare magnum' of the author's production, shows something useful as regards the issues and how to face them.